Cellulose Nanofiber-Based Hydrogels Embedding 5-FU Promote Pyroptosis Activation in Breast Cancer Cells and Support Human Adipose-Derived Stem Cell Proliferation, Opening New Perspectives for Breast Tissue Engineering - Liliana-Roxana Balahura; Sorina Dinescu; Mihaela Balaș; Alexandra Cernencu; Adriana Lungu; George Mihail Vlăsceanu; Horia Iovu; Marieta Costache (MDPI AG, 2021)
The structure and biocompatibility analysis of a hydrogel based on cellulose nanofibers (CNFs) combined with alginate/pectin (A.CNF or P.CNF) and enriched with 1% or 5% 5-FU revealed more favorable properties for the cellular component when pectin was dispersed within CNFs. 5-Fluorouracil (5-FU) is an antimetabolite fluoropyrimidine used as antineoplastic drug for the treatment of multiple solid tumors. 5-FU activity leads to caspase-1 activation, secretion and maturation of interleukins (IL)-1, IL-18 and reactive oxygen species (ROS) generation. Furthermore, the effects of embedding 5-FU in P.CNF were explored in order to suppress breast tumor cell growth and induce inflammasome complex activation together with extra- and intracellular ROS generation. Exposure of tumor cells to P.CNF/5-FU resulted in a strong cytotoxic effect, an increased level of caspase-1 released in the culture media and ROS production-the latter directly proportional to the concentration of anti-tumor agent embedded in the scaffolds. Simultaneously, 5-FU determined the increase of p53 and caspase-1 expressions, both at gene and protein levels. In conclusion, P.CNF/5-FU scaffolds proved to be efficient against breast tumor cells growth due to pyroptosis induction. Furthermore, biocompatibility and the potential to support human adipose-derived stem cell growth were demonstrated, suggesting that these 3D systems could be used in soft tissue reconstruction post-mastectomy.